A NOVEL THAT SWIRLS AROUND: PARALLEL READING OF KARAHASAN'S "EASTERN DIWAN" AND "SIMON THE MIRACLEWORKER" BY DANILO KIŠ (Heritage, 2023)
The paper draws attention to the intertextual connections between Karahasan's novel "Eastern Diwan" and Kiš's story "Simon the Miracle Worker," the first in the thematic collection "Encyclopedia of the Dead,"  based on thematic, motive and structural similarities. Both literary works are characterized by documentary, a recognizable postmodernist procedure that results in the demystification of the basic text. As a result, the postmodernist tendency for one text to aspire to another as a reflection of reality or an idea is highlighted. By complicating the story and inserting texts written into each other, a structure that mimics the idea of both literary works where the variations arise from the Truth is ensured and that each has its own relationship to the Truth while building another story as a variant or an Illusion.
Keywords: Dževad Karahasan, Danilo Kiš, intertextuality, documentary, archetype, Truth, Illusion